Reliability of "Google" for obtaining medical information - Mihir Kothari; Samita Moolani (Indian Journal of Ophthalmology, 2015)
Internet is used by many patients to obtain relevant medical information. We assessed the impact of "Google" search on the knowledge of the parents whose ward suffered from squint. In 21 consecutive patients, the "Google" search improved the mean score of the correct answers from 47% to 62%. We found that "Google" search was useful and reliable source of information for the patients with regards to the disease etiopathogenesis and the problems caused by the disease. The internet-based information, however, was incomplete and not reliable with regards to the disease treatment.